Repeated oral dose of monocrotophos in goats its bioaccumulation - Arifin, M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1997)
Monocrotophos bioaccumulation in goats was studied through repeated oral doses followed by serial slaughter of the animals. Twelve yearling local male goats were fed commercial concentrate (17% CP), napier grass ad libitum, and were daily with 120 g orally treated daily with 0.006 mg/kg body weight of ¹⁴C monocrotophos. The animals were randomly selected for slaughter on days 3, 6, 9, 12, 15, 18, 21, 24, 27, 30, 33, and 36 of the dosing period. Urine and feces were collected separately for the measurement of monocrotophos elimination. The liver, biceps femoris, longissimus dorsi, and abdominal fat were also collected for monocrotophos residue analysis through radioactive measurement.